Integrating Augmented Reality (AR) In EFL Class For Teaching Vocabulary - Sadikin, Irma Savitri; Martyani, Erista (PROJECT (Professional Journal of English Education), 2020)
In the industrial era 4.0, the use of technology in the learning process is an important element. Teachers need to be more technologically in their teaching process since the use of technology has become a lifestyle. Augmented Reality (AR) is an interactive experience of a real-world environment which is considered effective as good medium in learning especially in English vocabulary. This article aims to explore the use of AR for young learners by comparing it with conventional paper flashcards. This method used quantitative research or more specifically quasi-experimental design at the second grade of Primary school in Padalarang. The data of the research was obtained from pre-test and post-test and it was analyzed by using SPSS 22 for windows. The results showed that both AR and conventional flashcard could significantly improve young learners’ vocabulary. However, the mean score of posttest in experimental class was 74.83 and 62.5 for control class. The data analysis revealed that the null hypothesis was rejected. In other word, the posttest score of experimental class was higher than control class. In summary, learning English vocabulary through augmented reality (AR) could improve students’ vocabulary mastery. It made young learners more engaged and excited to learn English vocabulary.